Anatomical and Histochemical Responses of Vetiver Grass (Chrysopogon zizanioides L. Roberty) to Phytoremediation Ability of Liquid Batik Waste - Alfera Linggawati; Maryani; Andhika Puspito Nugroho; Diah Rachmawati (Environment and Natural Resources Journal, 2022)
Due to poor management of Indonesian batik waste, pollutants are discharged directly into rivers and absorbed from soil, causing environmental pollution. A phytoremediation strategy was chosen as one of the environmentally friendly and community-implementable solutions. Vetiver grass (Chrysopogon zizanioides L. Roberty) is a type of Poaceae plant that is suitable for the phytoremediation process of batik waste. This study analyzed the anatomical responses, distribution of secondary metabolites as defense compounds, and the ability to absorb heavy metals contained in liquid batik waste. Liquid batik waste was applied as plants irrigation at various concentration (0%, 25%, 50%, 75%, and 100%) for 60 days. Vetiver grass was able to grow well in the applied concentrations range. The results showed that vetiver grass roots could absorb Cu metal better than in the leaves. This plant can be stated to be able to absorb Cu better than Al. Liquid batik waste significantly (p<0.05) affected most of the observed anatomical parameters, where concentrations of 75% and 100% were the most influential concentrations according to the DMRT test with a 95% confidence level. The histochemical analysis found that there was an increase in the distribution of lignin, phenolic compound, and terpenoids in the tissues composed of roots and leaves along with the increase in the concentration of the waste applied.